Sistem Penentuan Jarak Terdekat Menuju Fasilitas Kesehatan Dengan Metode Algoritma Greedy - Muhammad Irfansyahfalah; Roeslan Djutlov (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
This research aims to find healthcare facilities through determining the nearest distance using a website. In this study, it is conducted using a mobile phone that utilizes GPS. The situation here is when the user is in a certain location and wants to find healthcare facilities. To address the above issue, a system is created to determine the nearest distance using a mobile phone and GPS during website access. Then, the website will directly recommend the nearest healthcare facility locations within a 10 km radius when the 'get my location' button is clicked. Subsequently, LeafletJS will provide an overview of the distance between the user and the healthcare facility location. The method used in this research is the greedy algorithm when processing the determination of the nearest distance from the user's location to reachable healthcare facilities. The results of this research indicate that the system for determining the nearest distance to healthcare facilities using the website can be accessed without login.